PERILAKU PENCARIAN INFORMASI MELALUI JURNAL ELEKTRONIK OLEH MAHASISWA PRODI ILMU PERPUSTAKAAN MENGGUNAKAN MODEL ELLIS - Anggia Fitra Hutapea; Ruslan Ruslan; Asnawi Asnawi (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2021)
Information seeking behavior is a micro-level search behavior, which is shown by a person when interacting with all types of information systems. This study examines information seeking behavior through electronic journals using the Ellis model which has 8 (eight) stages of information search, namely starting, chaining, browsing, differentiating, monitoring, extracting, verification, and ending. This study also examines the constraints faced by Library Science students in searching for information through electronic journals. This study uses quantitative methods using purposive sampling technique, with a total of 57 respondents. The results showed that there was a small proportion of Library Science students who did not start, namely collecting initial information through experts, lecturers, or friends. At the chaining stage, some students do not use bibliographies of books, journals, scientific papers and also do not specify keywords before searching. At the browsing stage, a small proportion of students did not limit their search so that the information displayed did not come out of the desired topic. While the obstacles they face in searching for electronic journals are networks that often have problems, difficulty in determining keywords, limited information displayed in electronic journals, limited foreign language skills, and also advertisements that appear in electronic journals.